Heavy LIFting: tumor promotion and radioresistance in NPC - Luftig, Micah (The Journal of Clinical Investigation, 2013)
The epithelial-derived nasopharyngeal carcinoma (NPC) is a rare tumor in most of the world; however, it is common in southern China, northern Africa, and Alaska. NPC is often left undiagnosed and untreated until a late stage of disease. Furthermore, while radiation therapy is effective against this tumor, local recurrence due to radioresistance is an important clinical problem. In this issue, Liu et al. report on their identification of the IL-6 family cytokine leukemia inhibitory factor (LIF) as a serum predictor of local NPC recurrence following radiation therapy. The authors developed this initial finding to discover a role for the LIF/LIFR/mTORC1 signaling axis in NPC tumor cell growth as well as radioresistance.